Rsearch progress on the relationship between aging and microbiota in sarcopenia - Cheng, Jing-Ping; Chen, Xiang; Chen, Jia-Xin (Frontiers in Medicine, 2025)
Sarcopenia is an age-related skeletal muscle disease associated with adverse outcomes such as falls, decreased function, frailty, and death, and is a significant global public health problem that impairs the functioning of individuals. Aging is intensifying, the number of people with sarcopenia is increasing, and there are currently no specific treatment drugs for sarcopenia. The clinical pathogenesis of sarcopenia is extremely complex, and the underlying mechanism of immunosenescence and dysbiosis associated with aging on sarcopenia is not well studied, and they are also potential therapeutic targets for sarcopenia. This review mainly discusses the relationship between sarcopenia from the perspective of intestinal microbiota dysbiosis and T cell changes in immunosenescence, and looks for promising targets for diagnosis or intervention of sarcopenia in the future, hoping to achieve early detection, early diagnosis and early treatment of sarcopenia and prolong the life span of healthy aging.